2012
DOI: 10.1142/s0217595912500200
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-on-Line Scheduling Problem of Two Parallel Machines With Common Maintenance Time

Abstract: In this paper, we consider a semi-on-line scheduling problem of two identical machines with common maintenance time interval and nonresumable availability. We prove a lower bound of 2.79129 on the competitive ratio and give an on-line algorithm with competitive ratio 2.79633 for this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Yuan et al (2012) obtained a best possible online algorithm for P 2 | online, r j , chains, p j = p | C max with a competitive ratio of ( Liu et al (2014) presented an optimal ϕ-competitive online algorithm where ϕ ≥ 1 is a solution of equation ϕ 3 +(α−1)ϕ 2 +(α 2 −α−1)ϕ−α 2 = 0. Cai et al (2012) gave a 2.796-competitive online algorithm for P 2 | online-list, nr-a, D | C max , and they showed that no online algorithm has a competitive ratio less than 2.791.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al (2012) obtained a best possible online algorithm for P 2 | online, r j , chains, p j = p | C max with a competitive ratio of ( Liu et al (2014) presented an optimal ϕ-competitive online algorithm where ϕ ≥ 1 is a solution of equation ϕ 3 +(α−1)ϕ 2 +(α 2 −α−1)ϕ−α 2 = 0. Cai et al (2012) gave a 2.796-competitive online algorithm for P 2 | online-list, nr-a, D | C max , and they showed that no online algorithm has a competitive ratio less than 2.791.…”
Section: Introductionmentioning
confidence: 99%